Resistance of pepper germplasm to Phytophthora capsici isolates colleted in northwest Spain - Andres Ares, J.L.=700 1 Rivera Martinez, A.; Fernandez Paz, J.
(Es, En)
ilus., 36 ref.
Keywords: CAPSICUM ANNUUM; INOCULACION; PHYTOPHTHORA CAPSICI; PATOGENESIS; ESPAÑA; PIMIENTO